Custom House, Trinidad. B.W.I. - (:unkn) unknown (Muir Marshall and Co., 2011)
A picture of Custom House, Trinidad. In this picture you can see boats docked and the train as it approaches custom house.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Harbors--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Railroad cars--Trinidad and Tobago; Customhouses--Trinidad and Tobago